Analisis Anggaran Biaya Operasional Sebagai Alat Pengawasan Pada Pt Akses Lintas Nusantara Branch Office Binjai - Langkat - Maf’ul Taufiq (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
The purpose of this study was to determine and analyze whether the operational cost budget has functioned as a monitoring tool at PT. Access Lintas Nusantara Branch Office Binjai - Langkat. In this study using a descriptive research approach, namely a study to compile, classify, interpret and interpret data so as to provide an overview of the problem of operating cost budget analysis as a company monitoring tool. The data analysis technique uses a descriptive method of accounting approach. Based on the results of data analysis and discussion, it can be seen that the supervision of the operating cost budget applied by PT. Access Lintas Nusantara Branch Office Binjai - Langkat has functioned well in carrying out operational activities. Supervision of the operating cost budget has been carried out by each sector in the company and a proposed operating cost budget for the sector is based on a 1 (one) year work plan which is then submitted to the head of finance at the end of September before the end of the current budget year. The company has not reached the budget target that was prepared due to deviations between the prepared budget and its realization.